MOF-derived composite materials and preparation methods and applications thereof
By using MOF-derived nickel diselenide composite material as the cathode material for aqueous zinc ion batteries, the problems of unstable structure and insufficient performance of the existing cathode material are solved, and high specific capacity effects with good conductivity, excellent rate performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202211655257.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-12-22
AI Technical Summary
The existing positive electrode materials of zinc ion batteries in water system have problems such as unstable structure, poor conductivity, poor rate performance and low capacity, which limit the performance of the battery.
The nickel diselenide (NiSe2-MOF) composite material derived from metal organic frame (MOF) is used as the positive electrode material, and the material is prepared by a one-step hydrothermal reaction, which has a stable and ordered structure and good conductivity.
The positive electrode material of zinc ion battery has achieved good conductivity, excellent rate performance, high cycle stability and high specific capacity, which has improved the overall performance of the battery.
Smart Images

Figure CN115799482B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to a MOF-derived composite material and a preparation method and application thereof. Background Art
[0002] With the continuous consumption of traditional energy that is difficult to renew and the growing demand for energy, solving the energy crisis and the resulting environmental problems has become a common consensus. Reducing the use of fossil fuels can alleviate the energy crisis to a certain extent, but more importantly, it is necessary to find new and reliable green energy. Among them, clean energy such as wind power, photovoltaics, and hydropower generation are often restricted by time, region, weather, etc., and cannot meet people's production needs anytime and anywhere, so these intermittent electric energies need to be stored before they can be used. Therefore, the research and development of efficient energy storage systems to better utilize clean energy has become an urgent problem to be solved, and secondary energy storage devices that can be recycled, highly efficient, and environmentally friendly are an important research direction of energy storage technology.
[0003] Among various new energy storage systems, aqueous zinc-ion batteries have attracted great attention due to the abundant resources and low price of the required metal material zinc, the safety and environmental protection of aqueous electrolytes, and the high ion conductivity. The most important part of aqueous zinc-ion batteries is the electrode material. The negative electrode material is mainly metallic zinc, and the positive electrode material is mainly transition metal compounds. Compared with the relatively high theoretical capacity of the zinc negative electrode (820mAh g -1 ), most of the metal compound cathode materials reported so far mainly include manganese-based compounds, vanadium-based compounds, Prussian blue analogs and polymers, etc., which have problems such as low capacity and poor rate performance of aqueous zinc-ion batteries due to their unstable structures. Designing and developing high-performance cathode materials has become the key to the development of aqueous zinc-ion batteries. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a metal organic framework (MOF) derived composite material, which has a stable and orderly structure and has good conductivity, good rate performance, cycle stability and high specific capacity when used as a positive electrode of a zinc ion battery.
[0005] The invention also provides a method for preparing a MOF-derived composite material.
[0006] The invention also provides a positive electrode.
[0007] The invention also provides a lithium ion battery.
[0008] According to one aspect of the present invention, a MOF-derived composite material is provided, wherein the composite material is a MOF-derived nickel diselenide (NiSe2-MOF) composite material.
[0009] The MOF-derived nickel diselenide composite material of the present invention is a thickened nanosheet stacking structure.
[0010] According to another aspect of the present invention, a method for preparing a MOF-derived composite material is provided. In this method, a nickel source, an organic ligand and a selenium source are dissolved in a solvent, and the MOF-derived composite material can be prepared by a one-step hydrothermal reaction.
[0011] The present invention prepares a sheet-like NiSe2-MOF composite material by hydrothermal selenization. The method only requires one step of hydrothermal reaction, is simple to operate, has easy and convenient raw materials, is low in cost, has low energy consumption, is easy to implement, and is suitable for large-scale industrial production.
[0012] In some embodiments of the present invention, the nickel source is at least one of nickel nitrate, nickel chloride or nickel sulfate.
[0013] In some embodiments of the present invention, the organic ligand is at least one of pure terephthalic acid, polyvinyl pyrrolidone or 2-methylimidazole.
[0014] In some embodiments of the present invention, the selenium source is at least one of selenium powder, selenium dioxide and sodium selenide.
[0015] In some preferred embodiments of the present invention, the concentration of the fixed nickel salt is 10 to 40 mmol L -1 ; preferably about 10 to 30 mmol L -1 .
[0016] In some preferred embodiments of the present invention, the molar ratio of the nickel source, the organic ligand and the selenium source is 1:0.3~3:0.3~2; preferably, the molar ratio of the nickel source, the organic ligand and the selenium source is 1:0.5~2:0.5~1.5; preferably, the molar ratio of the nickel source, the organic ligand and the selenium source is 1:0.7~2:0.5~1.5; preferably, the molar ratio of the nickel source, the organic ligand and the selenium source is about 1:1:1.
[0017] In some embodiments of the present invention, the solvent is an organic solvent; preferably, the organic solvent includes but is not limited to at least one of N,N-dimethylformamide, methanol, ethanol and water.
[0018] In some embodiments of the present invention, the solvent further comprises an alkaline solution; preferably, the alkaline solution includes but is not limited to at least one of a sodium hydroxide solution, a potassium hydroxide solution, a lithium hydroxide solution and a zinc hydroxide solution.
[0019] The concentration of the alkaline solution is 0-1M; the volume ratio of the organic solvent to the alkaline solution is 4-1:1.
[0020] In some preferred embodiments of the present invention, the concentration of the alkaline solution is 0 to 1 mol L -1 The addition of alkaline solution is beneficial to the dissolution of PTA. Preferably, the concentration of the alkaline solution is about 0.4 mol L -1 .
[0021] In some preferred embodiments of the present invention, the volume ratio of the organic solvent to the alkaline solution is 4-1:1; the volume ratio of the organic solvent to the alkaline solution is 4-2:1; more preferably, the volume ratio of the organic solvent to the alkaline solution is about 4-3:1.
[0022] In some preferred embodiments of the present invention, the organic solvent is at least one of N,N-dimethylformamide (DMF), methanol, ethanol and water; preferably, the organic solvent is N,N-dimethylformamide.
[0023] In some preferred embodiments of the present invention, the alkaline solution is at least one of a sodium hydroxide solution, a potassium hydroxide solution, a lithium hydroxide solution and a zinc hydroxide solution.
[0024] In some embodiments of the present invention, the temperature of the hydrothermal reaction is 100-180°C; preferably, the temperature of the hydrothermal reaction is 120-180°C; preferably, the temperature of the hydrothermal reaction is 140-180°C; more preferably, the temperature of the hydrothermal reaction is about 160°C.
[0025] In some embodiments of the present invention, the hydrothermal reaction time is 6 to 16 hours; preferably, the hydrothermal reaction time is 8 to 14 hours; preferably, the hydrothermal reaction time is 10 to 14 hours; more preferably, the hydrothermal reaction time is about 12 hours.
[0026] According to yet another aspect of the present invention, a positive electrode is provided, which comprises the above-mentioned MOF-derived composite material.
[0027] According to another aspect of the present invention, a zinc ion battery is provided, which comprises the above-mentioned positive electrode.
[0028] In some embodiments of the present invention, the zinc ion battery further comprises a separator, an electrolyte and a negative electrode.
[0029] In some preferred embodiments of the present invention, the separator is selected from glass fiber, the electrolyte comprises a soluble zinc salt, and the negative electrode is a zinc sheet.
[0030] As used herein, when used in connection with a numerical value, the term "about" is intended to include a set or range of numerical values. For example, "about X" includes a numerical range of ±10%, ±5%, ±2%, ±1%, ±0.5%, ±0.2% or ±0.1% of X, where X is a numerical value. In one embodiment, the term "about" refers to a numerical range of 5% more or less than a specific value. In another embodiment, the term "about" refers to a numerical range of 2% more or less than a specific value. In another embodiment, the term "about" refers to a numerical range of 1% more or less than a specific value.
[0031] The MOF-derived nickel diselenide composite material of the present invention has a stable and orderly structure, and when used as a positive electrode of a zinc ion battery, has good electrical conductivity, good rate performance, cycle stability and high specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 a and Figure 1 b are SEM images of the nickel-based metal organic framework (Ni-MOF) material prepared in Example 1 and the MOF-derived nickel diselenide (NiSe2-MOF) composite material prepared in Example 2;
[0033] Figure 2 is the X-ray diffraction pattern of the Ni-MOF material prepared in Example 1 and the NiSe2-MOF composite material prepared in Example 2;
[0034] Figure 3 is the electrochemical performance diagram of the Ni-MOF material prepared in Example 1 and the NiSe2-MOF composite material electrode prepared in Example 2, wherein Figure 3 a is the AC impedance diagram; Figure 3 b is in 3Ag -1 Constant current charge and discharge curve under current density;
[0035] Figure 4 : is the electrochemical performance diagram of the Ni-MOF material prepared in Example 1 and the NiSe2-MOF composite material electrode prepared in Example 2, wherein: Figure 4 a is the rate performance diagram; Figure 4 b is at 8A·g -1 Cycle life curve under current density. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0037] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0038] Example 1
[0039] This embodiment prepares a nickel-based metal organic framework material, and the specific steps are as follows:
[0040] Dissolve 1mmol nickel nitrate hexahydrate and 1mmol pure terephthalic acid in 20mL N,N-dimethylformamide and 5mL 0.4mol L -1 The mixed solution of sodium hydroxide solution was transferred into a 50 mL polytetrafluoroethylene liner and placed in a reactor after being fully stirred. The reactor was subjected to hydrothermal reaction at 160° C. in an oven for 12 h.
[0041] After the reaction is completed, the product is centrifuged and dried to obtain the final product, nickel-based metal organic framework (Ni-MOF) material.
[0042] Example 2
[0043] This example prepares a MOF-derived nickel diselenide composite material, and the specific steps are as follows:
[0044] Dissolve 1mmol nickel nitrate hexahydrate, 1mmol pure terephthalic acid and 0.5mmol selenium dioxide in 20mL N,N-dimethylformamide and 5mL 0.4mol L -1 The mixed solution of sodium hydroxide solution was transferred into a 50 mL polytetrafluoroethylene liner and placed in a reactor after being fully stirred. The reactor was subjected to hydrothermal reaction at 160° C. in an oven for 12 h.
[0045] After the reaction is completed, the product is centrifuged and dried to obtain a MOF-derived nickel diselenide (NiSe2-MOF) composite material.
[0046] Embodiment 3-8
[0047] The methods of Examples 3-8 are the same as those of Example 2. Based on the scheme of Example 2, MOF-derived nickel diselenide composite materials are prepared by adjusting the molar ratio of nickel nitrate to terephthalic acid and selenium dioxide and the time of the hydrothermal reaction. The relationship is shown in Table 1.
[0048] Performance Testing
[0049] The nickel-based metal organic framework material prepared in the above example and the MOF-derived nickel diselenide composite were prepared into the positive electrode of the aqueous zinc ion battery and used to test the electrochemical performance:
[0050] A homogenous slurry containing 80 wt% nickel-based metal organic framework or MOF-derived nickel diselenide composite material, 10 wt% acetylene black (conductive agent) and 10 wt% PVDF (binder) was prepared in an appropriate amount of DMF and then uniformly coated on a conductive substrate carbon paper and then vacuum dried at 60 °C overnight to form a working electrode. The loading of active material on the working electrode was about 2.2-2.4 mg cm -2 The following electrochemical performance tests were all conducted in an electrolytic cup environment with an electrolyte of 3 mol L - 1 KOH and 0.2 mol L -1 The aqueous solution of Zn(Ac)2, the positive electrode is the prepared carbon paper coated with active materials, the negative electrode is zinc sheet, and the electrochemical workstation is CHI660E.
[0051] The effects of different hydrothermal reaction conditions on the electrochemical properties of the materials prepared in Examples 1-8 are shown in Table 1.
[0052] Table 1
[0053]
[0054]
[0055] Figure 1 a. Figure 1 b are SEM images of the Ni-MOF material prepared in Example 1 and the NiSe2-MOF composite material prepared in Example 2. It can be seen from the figure that the Ni-MOF material presents a flower cluster structure formed by stacking nanosheets; the NiSe2-MOF composite material prepared in Example 2 presents a thickened nanosheet stacking structure. As the amount of selenium increases, the thickness of the nanosheets will continue to increase and gradually form a block structure.
[0056] from Figure 2 It can be clearly seen from the XRD diagram that the addition of selenium dioxide in the reaction causes the characteristic peak of Example 2 to change to nickel diselenide.
[0057] from Figure 3 It can be seen from a that the impedance of the NiSe2-MOF composite material prepared in Example 2 is significantly lower than that of the Ni-MOF material prepared in Example 1; Figure 3In b, the constant current charge-discharge curve of the Ni-MOF composite material electrode prepared in Example 2 is significantly better than that of the Ni-MOF material electrode prepared in Example 1.
[0058] from Figure 4 It can be seen from a that although the initial specific capacitance of the Ni-MOF material electrode prepared in Example 1 is slightly higher than that of the NiSe2-MOF composite material electrode prepared in Example 2, the rate performance of the NiSe2-MOF electrode prepared in Example 2 is significantly better than that of the Ni-MOF electrode prepared in Example 1; Figure 4 It can also be seen from b that the maximum specific capacitance and capacity retention rate after cycling of the NiSe2-MOF electrode prepared in Example 2 are better than those of the Ni-MOF electrode prepared in Example 1.
[0059] In addition, it can be seen from Table 1 that the ratio of nickel source to organic ligand and selenium source and the time of hydrothermal reaction have a significant effect on the performance of the MOF-derived nickel diselenide composite material. The MOF-derived nickel diselenide composite material prepared under the preparation conditions of the present invention can obtain a material having good electrical conductivity, good rate performance, cycle stability and high specific capacity.
[0060] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a MOF-derived composite material, characterized in that: The nickel source, organic ligand and selenium source are dissolved in a solvent, and a MOF-derived nickel diselenide composite material can be prepared by a one-step hydrothermal reaction; The nickel source is at least one of nickel nitrate, nickel chloride or nickel sulfate; the organic ligand is at least one of pure terephthalic acid, polyvinyl pyrrolidone or 2-methylimidazole; the selenium source is at least one of selenium powder, selenium dioxide and sodium selenide; The molar ratio of the nickel source, the organic ligand and the selenium source is 1:0.3-3:0.3-2; The temperature of the hydrothermal reaction is 100-160° C.; the time of the hydrothermal reaction is 6-16 hours.
2. The preparation method according to claim 1, characterized in that: The solvent is a mixture of an organic solvent and an alkaline solution.
3. The preparation method according to claim 2, characterized in that: The organic solvent includes at least one of N,N-dimethylformamide, methanol, ethanol and water; the alkaline solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, lithium hydroxide solution and zinc hydroxide solution.
4. The preparation method according to claim 2, characterized in that: The concentration of the alkaline solution is 0-1M; the volume ratio of the organic solvent to the alkaline solution is 4-1:
1.
5. A MOF-derived composite material, characterized in that It is prepared by the preparation method described in any one of claims 1 to 4.
6. The MOF-derived composite material according to claim 5, characterized in that The MOF-derived composite material has a nanosheet stacking structure.
7. A positive electrode, characterized in that It comprises the MOF-derived composite material according to any one of claims 5 to 6.
8. A zinc ion battery, characterized in that It comprises the positive electrode according to claim 7.
Citation Information
Patent Citations
Method for preparing aluminum battery positive electrode material by using MOF induced metal selenide
CN111180725A
Preparation method and application of sodium ion battery negative electrode material NiSe2@C microspheres
CN113422032A
Preparation method of nickel-based metal organic framework derived nickel diselenide / reduced graphene oxide composite material
CN113511647A